Positively charged nanofiltration membrane for magnesium-lithium separation and preparation method of positively charged nanofiltration membrane
Through the two-time interface polymerization and crown ether B15C5 modification methods, the magnesium lithium separation capability of the nanofiltration membrane is improved, efficient magnesium lithium separation and stable permeability are achieved, and the problem of poor separation of magnesium lithium in existing membranes in salt lake brine is solved.
Patent Information
- Application Number
- CN202510262550.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-06-03
AI Technical Summary
The existing nanofiltration membranes have poor magnesium-lithium separation effect in salt lake brine, especially the retention rate of magnesium ions and the magnesium-lithium separation factor still have room for improvement.
Through the two interfacial polymerization process, polyethyleneimine PEI and TMC were introduced for the first interfacial polymerization to form a preliminary polyamide layer; then the second interfacial polymerization was carried out to further increase the -NH2 content on the film surface and enhance the positive charge on the film surface, thereby strengthening the Donnan effect and improving the retention rate of magnesium ions. At the same time, the crown ether compound B15C5 was introduced to improve the hydrophilicity and water flux of the membrane.
The efficient retention of magnesium ions and significant separation of magnesium lithium were achieved. The retention rate of Mg2+ by BTB membrane can reach more than 99%, and the magnesium lithium separation factor reaches 57.2, which is 12.2 times that of unmodified membranes, and maintains stable permeability.
Smart Images

Figure CN120079239A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nanofiltration composite membranes, and particularly relates to a positively charged nanofiltration membrane for magnesium-lithium separation and a preparation method thereof. Background Art
[0002] Lithium is the lightest alkali metal element in nature, with excellent properties such as extremely high electrochemical activity, specific heat capacity, redox potential, etc., and is also called "white petroleum". Lithium and its compounds are widely used in batteries, lubricants, glass, ceramics, polymer production, air treatment, etc. Global lithium resources mainly exist in ores, salt lake brines and seawater. At present, the world's identified lithium resources are 97 million tons, of which 59% of the lithium resources are distributed in salt lakes. China is rich in lithium resources in salt lake brines, accounting for about 80% of the currently proven lithium resource reserves, and is mainly distributed in Tibet and Qinghai regions, but generally has the problem of a relatively high magnesium-lithium ratio. Traditional methods for extracting lithium from salt lakes mainly include precipitation method, adsorption method, calcination leaching method, solvent extraction method, electrodialysis method, etc., but these processes also have different defect limitations. Membrane separation process is a new type of efficient separation technology. Among them, nanofiltration (NF) membrane is a low-pressure driven membrane separation technology, with the pore size range belonging to the nanometer level, and the membrane structure has a charged property. In the NF process, the combined action of the Donnan effect, steric hindrance and dielectric repulsion acts on the mass transfer process, which enables the NF membrane to effectively intercept monovalent, divalent and multivalent ions, showing significant advantages in the field of magnesium-lithium separation of salt lake brines. Currently, commercial NF membranes are mainly prepared by the interfacial polymerization reaction of piperazine (PIP) and trimesoyl chloride (TMC). The hydrolysis of the groups makes these membranes negatively charged, and under the action of the Donnan effect, their rejection rate of magnesium ions is not high, and they perform poorly in the selective separation of calcium and magnesium ions. Developing high-performance positively charged nanofiltration membranes for extracting lithium from salt lakes has good development prospects.
[0003] In response to this, previous studies have shown that a new type of positively charged NF membrane with high permeability and excellent Mg 2+ / Li + separation factor is designed by interfacial polymerization. By mixing hydrophilic two-dimensional transition metal carbonitride (MXene) nanosheets into a polyethersulfone (PES) membrane substrate to enhance permeability, and then modifying the polyamide layer with crown ether molecule B15C5 to optimize the surface properties of the membrane, the B15C5-MX-NF membrane is prepared. Due to the enhanced interaction between the substrate membrane and polyethyleneimine (PEI) by the incorporation of MXene, the thickness of the polyamide (PA) layer is effectively reduced, and the addition of B15C5 provides an additional Li + permeation channel. Under the dual optimization of the membrane substrate and the PA layer, the permeability of the B15C5MX-NF membrane is improved, but the rejection ability of Mg 2+ and Mg2+ / Li + There is still much room for improvement in the separation factor. To obtain better Mg 2+ / Li + separation effect, previous research developed a secondary interfacial polymerization strategy for preparing high-performance nanofiltration membranes. They carried out the first interfacial polymerization (IP) reaction using PEI and cyanuric chloride (CC) on a PES hollow fiber substrate, and then reacted tris(2-aminoethyl)amine (TAEA) with the acyl chloride groups remaining after the first IP to increase the positive charge intensity on the membrane surface. Compared with the original membrane formed after the first IP, the TAEA-optimized membrane showed a high pure water permeability of 25.2 L·m -2 ·h -1 ·bar -1 at a working pressure of 2 bar, and the rejection rate for MgCl 2 was close to 90%.
[0004] Based on the above technical background analysis, it can be seen that: (1) Compared with negatively charged membranes, positively charged NF membranes can more effectively separate multivalent cations such as Ca 2+ and Mg 2+ to achieve an improvement in the Mg 2+ / Li + separation effect; (2) The crown ether structure can provide an additional permeation channel for Li + to further enhance the permeability of Li + and the hydrophilicity of the membrane; (3) Secondary interfacial polymerization can increase the positive charge and membrane thickness on the surface of the NF membrane, thereby improving the Mg 2+ / Li + selectivity. Therefore, a positively charged NF membrane that combines multiple coupling modification strategies, has excellent magnesium-lithium separation ability, and has high stability, and its preparation method are urgently needed in the current salt lake industry. SUMMARY OF THE INVENTION
[0005] In view of the above problems, the present invention uses a two-step interfacial polymerization process, for the first time introducing polyethyleneimine PEI and TMC for the first interfacial polymerization to form a preliminary polyamide layer; then carrying out a second interfacial polymerization to further increase the -NH 2The content is increased to enhance the positive charge on the membrane surface, thereby strengthening the Donnan effect, improving the rejection rate of magnesium ions, and achieving efficient magnesium-lithium separation. During the two interfacial polymerization processes, a crown ether compound B15C5 is introduced. B15C5 can improve the hydrophilicity and water flux of the membrane. The oxygen atoms in the B15C5 molecule can form hydrogen bonds with water molecules, promoting the transfer of water molecules within the membrane, thereby increasing the water flux of the membrane. In addition, the cavity size of the crown ether is between 0.17 - 0.22 nm, which is just between magnesium and lithium ions, enabling efficient separation of magnesium and lithium ions. At the same time, lithium ions exhibit strong binding force and strong complexation due to their diameter (0.16 nm) being extremely close to that of the crown ether.
[0006] The present invention is achieved by the following technical means, and the specific preparation steps are as Figure 1 shown:
[0007] The present invention first discloses a method for preparing a nanofiltration membrane for extracting lithium from high-magnesium-lithium ratio salt lake brine, including:
[0008] (1) First interfacial polymerization: Immerse a commercial PES membrane with a pore size of 20 nm in the aqueous phase I solution for 1 min, take it out and air-dry it naturally, then place the air-dried PES membrane in the oil phase solution for reaction, and take it out and air-dry it naturally;
[0009] (2) Second interfacial polymerization: Immerse the membrane after the first interfacial polymerization in the aqueous phase II solution for 30 min. After the reaction, dry the membrane in a vacuum drying oven;
[0010] (3) Post-treatment: Take out the dried membrane and cool it, wash it repeatedly with distilled water to remove surface by-products, and store the membrane in distilled water and refrigerate it at 4 °C to obtain the product.
[0011] Furthermore, before use, the commercial PES membrane in step (1) further includes: immersing the commercial PES membrane in distilled water at room temperature for 24 h.
[0012] Furthermore, the aqueous phase I solution in step (1) includes: 0.2 g of PEI, 0.04 g of SDS, 0.04 g of Na 2 CO 3 , 0.04 g of B15C5, and 40 mL of distilled water.
[0013] Furthermore, the oil phase in step (1) is: 40 ml of n-hexane solution, where the mass fraction of TMC is 0.2 wt%.
[0014] Furthermore, the reaction time for placing the air-dried PES membrane in the oil phase solution in step (1) is 3 min.
[0015] Further, the aqueous phase II solution in step (2) includes: 0.4 g of PEI, 0.04 g of SDS, 0.04 g of Na 2 CO 3 , 0.04 g of B15C5, and 40 mL of distilled water.
[0016] Further, the drying temperature of the vacuum drying oven in step (2) is 80 °C, and the drying time is 8 - 10 min.
[0017] The present invention also discloses a nanofiltration membrane for extracting lithium from high magnesium - lithium ratio salt lake brine prepared by any of the above - mentioned preparation methods.
[0018] The beneficial effects of the present invention are as follows:
[0019] 1. The preparation method of the present invention endows the membrane with excellent magnesium - lithium separation ability
[0020] Through the secondary interfacial polymerization process combined with crown ether (B15C5) modification, a nanofiltration membrane (BTB membrane) with a double - layer lithium - ion permeation channel is prepared. First, a commercial PES membrane with a pore size of 20 nm is selected as the substrate membrane. After pretreatment, the first and second interfacial polymerizations are carried out respectively. The first interfacial polymerization uses an aqueous phase I solution (0.2 g of PEI, 0.04 g of SDS, 0.04 g of Na 2 CO 3 , 0.04 g of B15C5, and 40 mL of distilled water) and an oil phase (40 ml of n - hexane solution, where the mass fraction of TMC is 0.2 wt%). The second interfacial polymerization uses an aqueous phase II (0.4 g of PEI, 0.04 g of SDS, 0.04 g of Na 2 CO 3 , 0.04 g of B15C5, and 40 mL of distilled water). The experimental results show that after the secondary interfacial polymerization, the surface charge of the membrane is significantly improved. The rejection rate of the BTB membrane for Mg 2+ can reach more than 99%, which is much higher than 81.2% of the unmodified membrane (PT membrane). At the same time, the magnesium - lithium separation factor of the BTB membrane reaches 57.2, which is 12.2 times that of the unmodified membrane. Through the synergistic effect of secondary interfacial polymerization and crown ether modification, the BTB membrane significantly improves the magnesium - lithium separation ability and can effectively meet the separation requirements of high magnesium - lithium ratio salt lake brine.
[0021] 2. The preparation method of the present invention endows the membrane with stable permeation performance
[0022] Under a pressure of 4 bar, the pure water permeation flux and salt solution rejection rate of the BTB membrane are tested. The experimental results show that the water permeation flux of the BTB membrane reaches 8.2 L·m -2 ·h -1 ·bar -1, compared with the unmodified membrane (PT membrane), the permeation performance remains stable. Although the secondary interfacial polymerization increases the membrane thickness, due to the enrichment of surface -NH 2 and the modification of hydrophilic B15C5, the surface hydrophilicity of the membrane is significantly improved, ensuring stable permeation performance. After the secondary interfacial polymerization and crown ether modification, the BTB membrane not only maintains a high magnesium - lithium separation ability but also sustains stable permeation performance, ensuring the high efficiency and durability of the membrane in practical applications.
[0023] 3. Experimental Scheme for the Preparation Method of the Present Invention Endowing the Membrane with Excellent Practical Application Ability
[0024] Using actual brine (Qarhan Salt Lake, China; Mg 2+ / Li + ratio of 928.6:1) to conduct a two - stage separation test on the BTB membrane. The permeate after the first separation is used as the feed liquid for the second separation, and the concentrations of Mg 2+ and Li + at each stage are measured respectively. The experimental results show that after two - stage separation, the Mg 2+ concentration is reduced to 2.9 ppm, achieving a removal rate of 99.8%. At the same time, the magnesium - lithium ratio is reduced from 928.6 to 1.9, realizing 488.7 - fold enrichment of Li + . During the 24 - hour continuous test, the ion flux and Mg 2 + interception rate of the membrane remain stable. The BTB membrane exhibits excellent separation performance and long - term stability in the actual brine test, can effectively treat complex brine systems with a high magnesium - lithium ratio, and has broad practical application prospects. Brief Description of the Drawings
[0025] Figure 1 It is the preparation flow chart of the BTB membrane of the present invention.
[0026] Figure 2 It is the Zeta potential diagram of PT, BT, PTP and BTB membranes.
[0027] Figure 3 (a) is the flux of PT, BT, PTP and BTB membranes and the interception of magnesium and lithium in single - solution; 3(b) is the magnesium - lithium separation factor when PT, BT, PTP and BTB membranes separate the mixed solution with a magnesium - lithium ratio of 20; 3(c) is the magnesium - lithium separation factor of BTB at different magnesium - lithium ratios.
[0028] Figure 4 (a) is the schematic diagram of two - stage membrane separation; 4(b) is the long - term separation test of the membrane; 4(c) is the concentration of magnesium and lithium ions under two - stage separation. Detailed Embodiments
[0029] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be described clearly and completely below. For those not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. For reagents or instruments without indicating the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0030] The following are the abbreviations and definitions of key terms related to the present invention:
[0031] NF: Nanofiltration; Donnan: Donnan; TMC: Trimesoyl chloride; MXene: Transition metal carbides and nitrides; PES: Polyethersulfone; PEI: Polyethyleneimine; PA: Polyamide; CC: Cyanuric chloride; IP: Interfacial polymerization; TAEA: Tris(2-aminoethyl)amine; PWP: Pure water permeability; PIP: Piperazine; B15C5: Benzo-15-crown-5; SDS: Sodium dodecyl sulfate; MOFs: Metal-organic frameworks.
[0032] Comparative Example 1
[0033] Aqueous phase I solution: 0.2 g of PEI, 0.04 g of SDS, Na 2 CO 3 0.04 g, 40 mL of distilled water.
[0034] Aqueous phase II solution: None.
[0035] Oil phase: 40 ml of n-hexane solution, where the mass fraction of TMC is 0.2 wt%.
[0036] First interfacial polymerization: Immerse the PES membrane in the aqueous phase I solution for 1 min, take it out and air-dry naturally to remove the water stains on the surface. Place the air-dried PES membrane in the oil phase solution and react for 3 min, then take it out and air-dry naturally to remove the excess solution on the surface.
[0037] Second interfacial polymerization: None.
[0038] Post-treatment: Take out the dried membrane and let it cool, wash it with distilled water multiple times to remove the excess by-products on the surface. Store the membrane in distilled water and refrigerate it at 4 °C for further use.
[0039] Comparative Example 2
[0040] Aqueous phase I solution: 0.2 g of PEI, 0.04 g of SDS, Na 2 CO 3 0.04 g, 0.04 g of B15C5, 40 mL of distilled water.
[0041] Aqueous phase II solution: None.
[0042] Oil phase: 40 ml of n-hexane solution with a mass fraction of TMC of 0.2 wt%.
[0043] First interfacial polymerization: Immerse the PES membrane in the aqueous phase I solution for 1 minute, take it out and air-dry naturally to remove the water stains on the surface. Place the air-dried PES membrane in the oil phase solution and react for 3 minutes, then take it out and air-dry naturally to remove the excess solution on the surface.
[0044] Second interfacial polymerization: None
[0045] Post-treatment: Take out the dried membrane and cool it, wash it several times with distilled water to remove the excess by-products on the surface. Store the membrane in distilled water and refrigerate it at 4°C for further use.
[0046] Comparative Example 3
[0047] Aqueous phase I solution: 0.2 g of PEI, 0.04 g of SDS, 0.04 g of Na 2 CO 3 , 40 mL of distilled water.
[0048] Aqueous phase II solution: 0.4 g of PEI, 0.04 g of SDS, 0.04 g of Na 2 CO 3 , 40 mL of distilled water.
[0049] Oil phase: 40 ml of n-hexane solution with a mass fraction of TMC of 0.2 wt%.
[0050] First interfacial polymerization: Immerse the PES membrane in the aqueous phase I solution for 1 minute, take it out and air-dry naturally to remove the water stains on the surface. Place the air-dried PES membrane in the oil phase solution and react for 3 minutes, then take it out and air-dry naturally to remove the excess solution on the surface.
[0051] Second interfacial polymerization: Immerse the membrane after the first interfacial polymerization in the aqueous phase II solution for 30 minutes. After the reaction, dry the membrane in a vacuum drying oven at 80°C for 8 - 10 minutes.
[0052] Post-treatment: Take out the dried membrane and cool it, wash it several times with distilled water to remove the excess by-products on the surface. Store the membrane in distilled water and refrigerate it at 4°C for further use.
[0053] Example 1
[0054] Aqueous phase I solution: 0.2 g of PEI, 0.04 g of SDS, 0.04 g of Na 2 CO 3 , 0.04 g of B15C5, 40 mL of distilled water.
[0055] Aqueous phase II solution: 0.4 g of PEI, 0.04 g of SDS, 0.04 g of Na 2 CO 3 , 0.04 g of B15C5, 40 mL of distilled water.
[0056] Oil phase: 40 ml of n-hexane solution, where the mass fraction of TMC is 0.2 wt%.
[0057] First interfacial polymerization: Immerse the PES membrane in the aqueous phase I solution for 1 min, take it out and air-dry it naturally to remove the water stains on the surface. Place the air-dried PES membrane in the oil phase solution and react for 3 min, then take it out and air-dry it naturally to remove the excess solution on the surface.
[0058] Second interfacial polymerization: Immerse the membrane after the first interfacial polymerization in the aqueous phase II solution for 30 min. After the reaction, dry the membrane in a vacuum drying oven at 80 °C for 8 - 10 min.
[0059] Post-treatment: Take out the dried membrane and let it cool, wash it with distilled water multiple times to remove the excess by-products on the surface. Store the membrane in distilled water and refrigerate it at 4 °C for further use.
[0060] For the above technical solutions, the following are some possible alternative solutions that can achieve the same or similar invention purposes to a certain extent, that is, to efficiently separate lithium ions from high magnesium-lithium ratio salt lake brines.
[0061] Alternative 1: Use other crown ether compounds
[0062] Other crown ether compounds such as 18-crown-6, dibenzo-18-crown-6, etc. can be used. These crown ethers have different cavity sizes and chemical structures, but they can also form complexes with lithium ions and magnesium ions, thus realizing magnesium-lithium separation. By adjusting the type and concentration of the crown ether, the separation performance of the membrane can be optimized.
[0063] Alternative 2: Use cyclodextrin compounds instead of crown ethers
[0064] Cyclodextrin compounds (such as α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin and their derivatives) can be used instead of crown ethers. Cyclodextrin compounds have a unique cyclic structure and cavity, and can form stable complexes with various ions and molecules, thus realizing selective separation.
[0065] Alternative 3: Use other monomers
[0066] Other positively charged polymers such as polyacrylamide, sodium polystyrene sulfonate, etc. can be used. These polymers can be introduced into the membrane by different chemical methods to endow the membrane surface with positive charges, thus enhancing the Donnan effect and improving the magnesium-lithium separation ability.
[0067] Alternative 4: Using functional materials
[0068] Other functional materials such as ionic liquids, MOFs, etc. can be combined. These materials can further enhance the selective separation ability of the membrane and improve the performance of the membrane.
[0069] Test Example 1
[0070] The samples prepared in the above respective embodiments were subjected to magnesium-lithium separation tests, and the test results are shown in Table 1:
[0071]
[0072] Test Example 2
[0073] To evaluate the surface charge characteristics of different membranes, we conducted Zeta potential tests and measured the Zeta potential values of four different membranes: the PT membrane was -4.3 mV, the BT membrane was -7.9 mV, the PTP membrane was 12.1 mV, and the BTB membrane was 8.5 mV. The results showed that the Zeta potentials of the PT membrane and the BT membrane were negative, indicating that their surfaces were negatively charged, which might be due to the -COOH groups generated after the hydrolysis of TMC, resulting in limited retention ability for magnesium ions. In contrast, the Zeta potentials of the PTP membrane and the BTB membrane were positive, indicating that their surfaces were positively charged, which benefited from the -NH 2 groups introduced during the secondary interfacial polymerization process, significantly enhancing the positive charge density on the membrane surface and thus improving the retention ability for magnesium ions. The Zeta potential of the BTB membrane was 8.5 mV, combining the dual advantages of secondary interfacial polymerization and B15C5 modification, showing higher magnesium-lithium separation factors and stable permeation performance in practical applications. The Zeta potential test results indicated that secondary interfacial polymerization significantly increased the positive charge density on the membrane surface, thereby enhancing the retention ability of the membrane for magnesium ions and the permeability of lithium ions, providing theoretical support for efficient magnesium-lithium separation.
[0074] Test Example 3
[0075] Such as Figure 3As shown in (a), to evaluate the permeation performance and ion rejection ability of different membranes, we tested the fluxes and rejection rates of four membranes: the flux of the PT membrane was 8.1 L·m-2·h-1, and the rejection rates for magnesium ions and lithium ions were 81.2% and 24.4% respectively; the flux of the BT membrane was 14.4 L·m-2·h-1, and the rejection rates for magnesium ions and lithium ions were 89.5% and 20.7% respectively; the flux of the PTP membrane was 4.9 L·m-2·h-1, and the rejection rates for magnesium ions and lithium ions were 97.6% and 56.9% respectively; the flux of the BTB membrane was 8.2 L·m-2·h-1, and the rejection rates for magnesium ions and lithium ions were 99.1% and 54.6% respectively. The results showed that the introduction of B15C5 significantly improved the flux and magnesium ion rejection ability of the membrane (such as the BT membrane), but the improvement in the selectivity for lithium ions by using B15C5 alone was limited; secondary interfacial polymerization significantly enhanced the magnesium ion rejection ability of the membrane (such as the PTP membrane and the BTB membrane), but due to the increase in membrane thickness, the flux decreased; the BTB membrane combined the dual advantages of secondary interfacial polymerization and B15C5 modification, significantly improving the magnesium ion rejection ability and lithium ion permeability while maintaining a relatively high flux, achieving efficient magnesium-lithium separation. In summary, the BTB membrane showed excellent performance in terms of flux and rejection, and could effectively meet the separation requirements of high magnesium-lithium ratio salt lake brines, with broad practical application prospects.
[0076] As Figure 3 (b) As shown, to evaluate the magnesium-lithium separation performance of different membranes, we tested the magnesium-lithium separation factors of four membranes: the magnesium-lithium separation factor of the PT membrane was 4.7, that of the BT membrane was 9.5, that of the PTP was 22.8, and that of the BTB membrane was 57.2. The experimental results showed that the magnesium-lithium separation ability of the PT membrane was relatively low, mainly relying on the polyamide layer formed by primary interfacial polymerization, with limited separation effect; the BT membrane significantly improved the magnesium-lithium separation factor to 9.5 by introducing B15C5, indicating that the crown ether structure of B15C5 provided an additional permeation channel for lithium ions and enhanced the selectivity; the PTP membrane further increased the magnesium-lithium separation factor to 22.8 through secondary interfacial polymerization, indicating that secondary polymerization significantly increased the positive charge density on the membrane surface and enhanced the magnesium ion rejection ability; the BTB membrane combined the dual advantages of secondary interfacial polymerization and B15C5 modification, with a magnesium-lithium separation factor as high as 57.2, which was 12.2 times that of the PT membrane, indicating its significant advantage in the separation of high magnesium-lithium ratio salt lake brines. In summary, the synergistic effect of secondary interfacial polymerization and B15C5 modification significantly improved the magnesium-lithium separation performance of the membrane, and the BTB membrane showed excellent separation ability and could efficiently meet the separation requirements of high magnesium-lithium ratio salt lake brines.
[0077] As Figure 3As shown in (c), to evaluate the separation performance of the BTB membrane under different magnesium-lithium ratios, we tested its magnesium-lithium separation factors in five mixed solutions with different magnesium-lithium ratios, and the results were 53.8, 59.1, 57.2, 61.4, and 62.3 respectively. The experimental results show that the BTB membrane exhibits excellent separation performance under different magnesium-lithium ratios, and the separation factor is stable between 53.8 and 62.3. This indicates that the BTB membrane can still maintain high-efficient magnesium-lithium separation ability in a high magnesium-lithium ratio environment, further verifying its applicability in the separation of actual salt lake brines. Conclusion: Through the synergistic effect of secondary interfacial polymerization and B15C5 modification, the BTB membrane significantly improves the selective separation performance of the membrane, can adapt to complex brine systems with different magnesium-lithium ratios, and has broad practical application prospects.
[0078] Test Example 4
[0079] As Figure 4 As shown in (b), to evaluate the long-term separation performance of the BTB membrane, we conducted a 24-hour continuous test to measure the changes in ion flux and magnesium ion rejection rate at different time intervals. The experimental results show that during the 24-hour continuous operation of the BTB membrane, both the ion flux and the magnesium ion rejection rate remain stable, and no obvious performance degradation occurs. Specifically, the magnesium ion rejection rate always remains above 98%, and the ion flux also maintains at a high level, indicating that the BTB membrane has excellent long-term stability in practical applications. Conclusion: Through the synergistic effect of secondary interfacial polymerization and B15C5 modification, the BTB membrane not only exhibits high-efficient magnesium-lithium separation ability but also has long-term stable use performance, can meet the continuous operation requirements of actual salt lake brine separation, and has broad practical application prospects.
[0080] As Figure 4 As shown in (c), to evaluate the separation performance of the BTB membrane in actual salt lake brines, we conducted a two-stage separation test to measure the changes in magnesium-lithium ratios at different stages. The experimental results show that the magnesium-lithium ratio of the initial feed liquid is 928.6. After the first separation, the magnesium-lithium ratio drops to 77.6, indicating that the BTB membrane significantly reduces the concentration of magnesium ions in the first stage; after the second separation, the magnesium-lithium ratio further drops to 1.9, indicating that the BTB membrane almost completely removes the remaining magnesium ions in the second stage and achieves high-efficient enrichment of lithium ions. The experimental results show that the BTB membrane exhibits excellent performance in the separation of actual salt lake brines, can significantly reduce the initial magnesium-lithium ratio from 928.6 to 1.9, and achieves 488.7-fold enrichment of lithium ions. Conclusion: Through the synergistic effect of secondary interfacial polymerization and B15C5 modification, the BTB membrane significantly improves the actual separation performance of the membrane, can effectively treat complex brine systems with high magnesium-lithium ratios, and has broad practical application prospects.
[0081] The preparation method of the nanofiltration membrane with ultra-high magnesium-lithium separation efficiency according to the present invention constructs a nanofiltration membrane with a double-layer lithium ion permeation channel through a secondary interfacial polymerization coupled with B15C5 modification process, thereby achieving efficient magnesium retention, an ultra-high magnesium-lithium separation factor, and stable actual brine permeation performance.
[0082] The above are only several specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. For those of ordinary skill in the art, all deformations directly derived or indirectly extended from the disclosed content of the present invention without departing from the principle of the present invention should be considered as the protection scope of the present invention. For the above technical solutions, the present invention can further improve the performance of the membrane by means of optimizing the polymerization conditions, introducing a bionic channel structure, combining adsorption-membrane separation technology, introducing zwitterionic polymer modification, etc.
Claims
1. A method for preparing a nanofiltration membrane for extracting lithium from salt lake brine with a high magnesium-to-lithium ratio, characterized in that: The steps include: (1) First interfacial polymerization: A commercial PES membrane with a pore size of 20 nm was placed in the aqueous phase I solution and immersed for 1 min, and then naturally air-dried after being taken out. The air-dried PES membrane was placed in the oil phase solution for reaction, and then naturally air-dried after being taken out. (2) Second interfacial polymerization: The membrane after the first interfacial polymerization was immersed in the aqueous phase II solution for 30 minutes. After the reaction was completed, the membrane was dried in a vacuum drying oven. (3) Post-processing: The dried membrane was taken out and cooled, and washed with distilled water for several times to remove surface byproducts. The membrane was stored in distilled water and refrigerated at 4°C.
2. The preparation method according to claim 1, characterized in that: The commercial PES membrane in step (1) further comprises, before use: The commercial PES membrane was immersed in distilled water at room temperature for 24 h.
3. The preparation method according to claim 1, characterized in that: The aqueous phase I solution in step (1) includes: 0.2 g PEI, 0.04 g SDS, 0.04 g Na2CO3, 0.04 g B15C5, and 40 mL distilled water.
4. The preparation method according to claim 1, characterized in that: The oil phase in step (1) is: 40 ml of n-hexane solution, in which the mass fraction of TMC is 0.2 wt%.
5. The preparation method according to claim 1, characterized in that: In step (1), the air-dried PES membrane is placed in the oil phase solution for a reaction time of 3 minutes.
6. The preparation method according to claim 1, characterized in that: The aqueous phase II solution in step (2) includes: 0.4 g PEI, 0.04 g SDS, 0.04 g Na2CO3, 0.04 g B15C5, and 40 mL distilled water.
7. The preparation method according to claim 1, characterized in that: The drying temperature of the vacuum drying oven in step (2) is 80° C. and the drying time is 8-10 min.
8. A nanofiltration membrane for extracting lithium from salt lake brine with a high magnesium-to-lithium ratio, prepared according to the preparation method of any one of claims 1 to 7.
Citation Information
Cited By
Crown ether functionalized negatively-charged nanofiltration membrane based on secondary interfacial polymerization as well as preparation method and application of crown ether functionalized negatively-charged nanofiltration membrane
CN120827815A
High-permeability and high-selectivity polyamide membrane for magnesium-lithium separation as well as preparation method and application of high-permeability and high-selectivity polyamide membrane
CN120827816A
A high-permeability and high-selectivity polyamide membrane for magnesium-lithium separation, a preparation method and application thereof
CN120827816B
Crown ether modified positively charged polyamide / carbon nanotube nanofiltration membrane as well as preparation method and application thereof
CN122273334A
A crown ether modified positively charged polyamide / carbon nanotube nanofiltration membrane, a preparation method and application thereof
CN122273334B